Asymmetric effects of oil shocks on economic policy uncertainty - Aimer, Najmi; Lusta, Abdulmula (Elsevier BV, 2022)
Abstract The aim of this paper is to investigate the asymmetric effects of the crude oil price on global economic policy uncertainty (EPU) using a nonlinear, autoregressive distributed lag approach. The results of the bounds test indicate that there is a long-run equilibrium relationship between economic uncertainty and crude oil price. Furthermore, we conclude that the long-run equilibrium relationship is a usual logical relationship and not a degraded relationship. The results of the asymmetric test also showed that the positive and negative shocks in oil prices do not have an asymmetric effect on the EPU in the long run and have an asymmetric effect in the short term. In addition, a negative shock may have a relatively greater effect in the long run compared to a positive shock while a positive shock may have a relatively greater impact in the short term compared to a negative shock. Our results are important to both investors interested in the oil market, as well as for policymakers.
Keywords: 8. Economic growth